ACTIVE METHODOLOGY WITH COMPANIONS IN THE PREVENTION OF PRESSURE INJURIES - Xavier, Débora; Feitosa, Yterfania Soares; Severino, Fernanda Gadelha; Morais, Leonice dos Santos; Terceiro, Anna Philomena de Alencar Brito; Nicodemo, Raquel Lucena; Alves, Jamille Soares Moreira (Cadernos ESP, 2024)
To report an educational strategy carried out with caregivers and family members of hospitalized patients to prevent pressure injuries using active methodology. This is an experience report on the application of an educational strategy regarding pressure injury prevention practices. It was carried out by a nursing academic, stoma therapists and col-laborators from an accredited public hospital in December 2023, being developed in three stages: Guidelines, Active Methodology and Content Synthesis. The participant observation method was used for data analysis. 27 family members, caregivers and companions participated. It was observed that the majority of participants were unaware of the strategies used to prevent injuries and, through educational action, it was possible to train and involve them in patient care, including prevention practices. In this way, collaboration between professionals, family members and patients aims to continuously improve services and the quality of care provided, providing a good experience for the patient.
Keywords: Health education; Pressure injury; Prevention